FINANCIAL MATHEMATICS, BANK CREDIT AND PERSONAL FINANCIAL DECISION-MAKING: A QUALI-QUANTITATIVE STUDY IN CALDAS NOVAS (GO) - Neto de Oliveira Felippe, José (Journal of Interdisciplinary Debates, 2025)
The expansion of access to bank credit in Brazil, intensified by the digitalization of financial services, has increased the complexity of personal financial decision-making, requiring a stronger understanding of financial mathematics concepts. This study aimed to analyze how the comprehension of simple and compound interest influences personal financial decision-making in the context of real bank credit offers. A quali-quantitative approach was adopted, structured in two complementary stages: a documentary analysis of public information available on the official websites of major financial institutions operating in Caldas Novas (GO), and a survey conducted with 405 respondents through a structured questionnaire. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through an interpretative analytical perspective. The results indicate that, despite the wide availability of digital information and frequent use of online simulators, a significant proportion of participants demonstrate insufficient understanding of compound interest, Total Effective Cost, and credit insurance, which is associated with higher levels of insecurity, financial difficulties, and lack of emergency savings. The findings show that access to information alone does not ensure informed financial decisions, revealing relevant implications for the credit market, consumer protection, and financial regulation. The study contributes by highlighting the need to integrate critical financial education, greater transparency in credit offers, and institutional strategies aimed at reducing financial vulnerability.